Language Brokering and Code Switching as Teaching and Learning Tools in Multilingual Settings: Reflections of Two Immigrant Children - Kemende Wunseh, Quinta; Charamba, Erasmos (Universitas Pendidikan Mandalika, 2023)
Language diversity is generally a norm in multilingual South African classroom. Orellana and GarcÃa (2014) describe how multilingual speakers need to learn tools to allow them to be flexible with their language skills. Language brokering and code-switching form part of the everyday teaching and learning tools needed in South African multilingual classroom setting. Data was collected by means of observation and semi-structured interviews. Snowball sampling was used to select Francophone immigrant children or learners who were observed outside the classroom in order to establish how they interacted with their peers on school playgrounds. Their personal narratives were collected and analyzed to enhance triangulation and thematic analysis was used to understand how immigrant children acted as language brokers. This research sets out to consolidate the position of language brokering and code-switching as pedagogically oriented language practices in a multilingual classroom setting. Using the sociocultural theories and the funds of knowledge (FoK), the current study rejects a deficit model, where linguistically and culturally diverse institutions of learning are reputed to be incapable of offering rich learning experiences and resources.